Micropropagation of Bauhinia variegata L. from Tissue Culture - Singh, BM; Wawrosch, C; Joshi, SD; Kopp, B (Nepal Journal of Science and Technology, 2013)
Bauhinia variegate L. is a multipurpose tree and its micropropagation holds great promise in agroforestry. The sterilized seeds were first inoculated on Murashige and Skoog (MS) medium. Nodal cuttings from these seedlings grown in vitro were used as explants for micropropagation. Nodal cutting inoculated on the medium with various concentrations of BAP (benzyl-aminopurine) and NAA (£- naphthalene acetic acid) and separately generated varied results. Best propagation was recorded on MS medium supplemented with 1.0 ?M BAP with 0.05 ?M NAA. Propagated plants were successfully acclimatized and rooted in pots (6 cm diameter) containing soil and sand in1:1 ratio and then finally transferred to the field. All the data generated were analysed statistically using SPSS statistical package. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 39-41 DOI: http://dx.doi.org/10.3126/njst.v13i1.7397